2014
DOI: 10.1097/fjc.0000000000000092
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Effects of Vasopressin

Abstract: Vasopressin is an essential hormone involved in the maintenance of cardiovascular homeostasis. It has been in use therapeutically for many decades, with an emphasis on its vasoconstrictive and antidiuretic properties. However, this hormone has a ubiquitous influence and has specific effects on the heart. Although difficult to separate from its powerful vascular effects in the clinical setting, a better understanding of vasopressin's direct cardiac effects could lead to its more effective clinical use for a var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 85 publications
0
23
0
Order By: Relevance
“…In addition, it has been demonstrated that the heart muscle has the capacity also to release VP [44,45]. Added to this is the number of studies which have shown that administration of VP in shock added to the endogenous release of VP often causes decreases in cardiac output and decreases in perfusion of the intestinal tract, kidneys and liver [43][44][45]. These affects can and often lead to lifethreatening situations.…”
Section: Open Accessmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, it has been demonstrated that the heart muscle has the capacity also to release VP [44,45]. Added to this is the number of studies which have shown that administration of VP in shock added to the endogenous release of VP often causes decreases in cardiac output and decreases in perfusion of the intestinal tract, kidneys and liver [43][44][45]. These affects can and often lead to lifethreatening situations.…”
Section: Open Accessmentioning
confidence: 99%
“…This controversy might be related to different actions on the major, surface coronaries versus the smaller arterioles deep within the walls of the ventricles. Another factor that has to be considered in all forms of circulatory shock, is that there is a massive release of VP from the paraventricular and supraoptic nuclei of the hypothalamus which often will reach levels in the blood which are from 20-200 times normal [45]. In addition, it has been demonstrated that the heart muscle has the capacity also to release VP [44,45].…”
Section: Open Accessmentioning
confidence: 99%
See 3 more Smart Citations